Some analysis and evaluation remarks on Vietnam science and technology - Duy, Bui The (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
During recent decades, Vietnam science and technology (S&T) has gained considerable results of development and given contributions to socio-economic development and national defense. From one side Vietnam S&T has got many achievements in enhancing highly S&T potentials, innovating and improving institutional structures of the country, and establishing initial backgrounds of S&T market. From another side, however, Vietnam S&T did not really become driving forces for socio-economic development. In this paper, we provide a summary of analysis and evaluation remarks on S&T development of Vietnam through stages as well as its actual situation. These considerations would permit to make some proposals for directions of S&T development of Vietnam in next stage. Code: 16080201